Perineural spread of pelvic malignancies to the lumbosacral plexus and beyond: clinical and imaging patterns - Capek, Stepan; Howe, Benjamin M.; Amrami, Kimberly K.; Spinner, Robert J. (Neurosurgical focus, 2015)
OBJECT Perineural spread along pelvic autonomie nerves has emerged as a logical, anatomical explanation for selected cases of neoplastic lumbosacral plexopathy (LSP) in patients with prostate, bladder, rectal, and cervical cancer. The authors wondered whether common radiological and clinical patterns shared by various types of pelvic cancer exist. METHODS The authors retrospectively reviewed their institutional series of 17 cases concluded as perineural tumor spread. All available history, physical examination, electrodiagnostic studies, biopsy data and imaging studies, evidence of other metastatic disease, and follow-up were recorded in detail. The series was divided into 2 groups: cases with neoplastic lumbosacral plexopathy confirmed by biopsy (Group A) and cases included based on imaging characteristics despite the lack of biopsy or negative biopsy results (Group B). RESULTS Group A comprised 10 patients (mean age 69 years); 9 patients were symptomatic and 1 was asymptomatic. The L5-S1 spinal nerves and sciatic nerve were most frequently involved. Three patients had intradural extension. Seven patients were alive at last follow-up. Group B consisted of 7 patients (mean age 64 years); 4 patients were symptomatic, 2 were asymptomatic, and 1 had only imaging available. The L5-S1 spinal nerves and the sciatic nerve were most frequently involved. No patients had intradural extension. Four patients were alive at last follow-up. CONCLUSIONS The authors provide a unifying theory to explain lumbosacral plexopathy in select cases of various pelvic neoplasms. The tumor cells can use splanchnic nerves as conduits and spread from the end organ to the lumbosacral plexus. Tumor can continue to spread along osseous and muscle nerve branches, resulting in muscle and bone "metastases." Radiological studies show a reproducible, although nonspecific pattern, and the same applies to clinical presentation.